Association Between Overweight and Obesity and Risk of Clinically Diagnosed Knee, Hip, and Hand Osteoarthritis: A Population‐Based Cohort Study. Issue 8 (27th July 2016) - Reyes, Carlen; Leyland, Kirsten M.; Peat, George; Cooper, Cyrus; Arden, Nigel K.; Prieto‐Alhambra, Daniel
Abstract : Objective: Studies of previous cohorts have demonstrated an association between a status of overweight/obesity and the presence of knee and hand osteoarthritis (OA). However, no data on the effect of these factors on the OA burden are available. The aim of the present study was to analyze the effect of being overweight or obese on the incidence of routinely diagnosed knee, hip, and hand OA. Methods: The study was conducted in a population‐based cohort using primary care records from the Sistema d'Informació per al Desenvolupament de l'Investigació en Atenció Primària database (>5.5 million subjects, covering >80% of the population of Catalonia, Spain). Participants were subjects ages ≥40 years who were without a diagnosis of OA on January 1, 2006 and had available body mass index (BMI) data. All subjects were followed up from January 1, 2006 to December 31, 2010 or to the time of loss to follow‐up or death. Measures included the World Health Organization categories of BMI (exposure), and incident clinical diagnoses of knee, hip, or hand OA according to International Classification of Diseases, Tenth Revision codes. Results: In total, 1, 764, 061 subjects were observed for a median follow‐up period of 4.45 years (interquartile range 4.19–4.98 years). Incidence rates (per 1, 000 person‐years at risk) of knee, hip, and hand OA were 3.7 (99% confidence interval [99% CI] 3.6–3.8), 1.7 (99% CI 1.7–1.8), and 2.6 (99% CI 2.5–2.7), respectively, among subjects in the normal weight category, and 19.5 (99% CI 19.1–19.9), 3.8 (99% CI 3.7–4.0), and 4.0 (99% CI 3.9–4.2), respectively, in those with a classification of grade II obesity. Compared to subjects with normal weight, being overweight or obese increased the risk of OA at all 3 joint sites, especially at the knee. A status of overweight, grade I obesity, and grade II obesity increased the risk of knee OA by a factor of 2‐fold, 3.1‐fold, and 4.7‐fold, respectively. Conclusion: Being overweight or obese increases the risk of hand, hip, and knee OA, with the greatest risk in the knee, and this occurs on a dose‐response gradient of increasing BMI.